An Ethical Framework for the Management of Pain in the Emergency Department. (16th July 2013) - Venkat, Arvind; Fromm, Christian; Isaacs, Eric; Ibarra, Jordan; ,; Goldstein, Joshua N.
Abstract Pain is a ubiquitous problem, affecting more than 100 million individuals in the United States chronically and many more in the acute setting. Up to three‐quarters of patients presenting to the emergency department (ED) report pain as a key component of their reasons for requiring acute care. While pain management is a fundamental component of emergency medicine (EM), there are numerous attitudinal and structural barriers that have been identified to effectively providing pain control in the ED. Coupled with public demands and administrative mandates, concerns surrounding ED pain management have reached a crisis level that should be considered an ethical issue in the profession of EM. In this article, the authors propose an ethical framework based on a combination of virtue, narrative, and relationship theories that can be used to address the clinical dilemmas that arise in managing pain in ED patients.